Hayton & Mitchell : commentary and cases on the law of trusts and equitable remedies - Mitchell, Charles; Hayton, David J. (Sweet & Maxwell, 2010)
Hayton & Mitchell is a thorough and perceptive treatment of modern English trust law in a unique combination of textbook and casebook in one compact volume. It is an ideal study aid for undergraduate and professional students, providing as it does, a detailed investigation of those 'grey' areas often favoured by examiners